2020
DOI: 10.1016/j.jocn.2020.07.034
|View full text |Cite
|
Sign up to set email alerts
|

Vasculitis-related stroke in young as a presenting feature of novel coronavirus disease (COVID19) – Case report

Abstract: COVID-19 is the disease caused by Novel Coronavirus (SARS-CoV-2) infection and world current main public health problem, due to its easy transmissibility and multiple clinical presentations. The main symptoms reported worldwide are dry cough, dyspnea, and fever, as well as anosmia and ageusia. COVID-19 diagnosis is made with RT-PCR, but many other complementary exams may be used to guide clinical practice, such as Chest Computerized Tomography (CT), showing ground glass opacities; increase in inflammatory mark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 4 publications
0
5
0
1
Order By: Relevance
“…Full-texts of the remaining 222 references were retrieved and screened for eligibility, and this process excluded an additional 115 references as the inclusion criteria was not met. This exclusion included articles with no access 28 , 29 , RT-PCR not clearly stated in the text 30 - 45 , case reports 46 - 97 , case seriess 98 - 113 , repeated datasetss 114 - 118 , and studies in specific groups 119 - 130 . A complete assessment was conducted for 107 references.…”
Section: Resultsmentioning
confidence: 99%
“…Full-texts of the remaining 222 references were retrieved and screened for eligibility, and this process excluded an additional 115 references as the inclusion criteria was not met. This exclusion included articles with no access 28 , 29 , RT-PCR not clearly stated in the text 30 - 45 , case reports 46 - 97 , case seriess 98 - 113 , repeated datasetss 114 - 118 , and studies in specific groups 119 - 130 . A complete assessment was conducted for 107 references.…”
Section: Resultsmentioning
confidence: 99%
“…De Sousa et al reported a 28-year-old male (SARS-CoV-2 IgM positive) presenting with intense headache, dysarthria and deviation of lip having MRI findings of cerebral vasculitis [ 112 ]. Bilateral trochlear nerve palsy due to cerebral vasculitis related to COVID-19 infection presenting with headache is also reported [ 113 ].…”
Section: Resultsmentioning
confidence: 99%
“…Cerebrovascular diseases 2 (28.6) (Xiong et al, 2020;Tiwari et al, 2021) 3 (13.6) (Asif and O' Mahony, 2020;Gulko et al, 2020;Dakay et al, 2021) 3 (15.8) (Cavalcanti et al, 2020;de Sousa et al, 2020;Dakay et al, 2021) 19 (31.7) (Al Saiegh et al, 2020;Cavalcanti et al, 2020;Cezar-Junior et al, 2020;Chia et al, 2020;Diaz-Segarra et al, 2020;Fara et al, 2020;Kantonen et al, 2020;Oxley et al, 2020;Pisano et al, 2020;Trifan et al, 2020a,b;Vu et al, 2020;Wang et al, 2020;Al-Mufti et al, 2021;Sabayan et al, 2021;Shah et al, 2021) 31 (43.1) (Agarwal et al, 2020;Anzalone et al, 2020;Cavalcanti et al, 2020;de Almeida Lima et al, 2020;Fabbri et al, 2021;Gupta et al, 2020;Heman-Ackah et al, 2020;Lapergue et al, 2020;Nicholson et al, 2020;Oxley et al, 2020;Patel et al, 2020;…”
Section: Age-associated Neurological Complications Of Covid-19unclassified